PENGGUNAAN MEDIA AUDIO-VISUAL PADA MATA PELAJARAN BAHASA ARAB - Intan Nurhasana (Al-Fikru : Jurnal Pendidikan Dan Sains, 2021)
The article with the title "The use of audio-visual media in Arabic subjects" describes the use of audio-visual media in learning. In general, Arabic learning only uses classical methods which tend to make students bored. Along with the development of the times, teachers are expected to be able to use various methods and media in the learning process. This is intended so that the learning process can take place to be more enjoyable so that the material provided can also be easily understood by students. Well-designed and creative learning by utilizing multimedia, within certain limits will be able to increase the likelihood of students to learn more to remember what they learn, better, and improve student performance in order to increase competency attainment. Media as an integral part of learning, this component needs to get the attention of teachers. The importance of media in facilitating students (learners), its presentation is adjusted to the learning objectives set. The presence of media in the learning process really helps students better understand what is being learned. Audio-visual is one of the media that can be used by teachers in learning Arabic. Moreover, with the development of technology that can make it easier for teachers and students to access and visit sites on the internet that provide information about learning Arabic. Keywords: media, audio-visual, Arabic lessons.